Impact of the Sr2+-Nd3+ heterovalent isomorphism on the luminescence of orthoborates in Sr3B2O6-NdBO3 system - Kuznetsov, Artem B.; Jamous, Ammar Y.; Svetlichnyi, Valerii A.; Shevchenko, Vyacheslav S.; Kokh, Alexander E.; Kokh, Konstantin A. (Journal of alloys and compounds)
The phase diagram of the Sr3B2O6-NdBO3 binary system was studied. The intermediate compound Sr3Nd2(BO3)4 can be synthesized over a wide range of compositions, from 27 to 70 mol.% NdBO3, at 1200◦C. The maximum luminescence of Nd in this solid solution was measured for the highest content of Sr. The partial substitution of Nd by 3 mol.% Sr in NdBO3 does not significantly affect the presence of concentration quenching. The phase exhibiting the strongest luminescence within the system is neodymium doped Sr3B2O6.